(3GfJgGc GdNUhUjI Hjf eSJNOeGJ hSGFd GdJhGUd GdGLJeGYi (B:s " (3OQGSI ai ShSjhdhLjG GdYfa HeOjfI GdbGgQI GdcHQi (B" / s - (3HGgQI GdSjO MSjf GdSjO,s; (3YOdi eMehO GdSeQis; (3CejQI YHO GdYXje aVd s (2024)
(3JgOa GdOQGSI Edi GdJYQa Ydi CHQR GfJgGcGJ GdNUhUjI GdJi JJYQV dgG eSJNOeGJ hSGFd GdJhGUd GdGLJeGYi, hCSHGH GdJYQV dJdc GdGfJgGcGJ, hGdBKGQ GdeJQJHI YdjgG , hGdhbha Ydi GdJOGHjQ GdhbGFjI dMeGjI GdNUhUjI, hcGfJ YjfI GdOQGSI ef GdeSJNOeGJ dhSGFd GdJhGUd GdGLJeGYi, hbO HdZJ MLegG (B200 (3eaQOI, hJhUdJ fJGFL GdOQGSI Edi(B: (3CHQR GdGfJgGcGJ GdJi JYQVJ dgG GdeSJNOeGJ gi CdaGX HPjFI Ch QehR Ch JYdjbGJ Ch fcGJ LfSjI(B"(3, h(B"(3GdGHJRGR GdLfSj YHQGdEfJQfJ(B"(3, h(B"(3EQSGd ebGWY ajOjh hEYdGfGJ EHGMjI(B". (3ef CHQR CSHGH hbhY GdeSJNOeGJ dGfJgGc GdNUhUjI (B"(3GdGfVeGe dCcKQ ef LQhH Ydi ehGbY GdJhGUd(B"(3, h(B"(3Mb eTGQcI GdeTGYQ eY GdBNQjf(B"(3, h(B"(3GdEMSGS HGdGfJeGA ddBNQjf(B".s
The study aims to identify the most significant privacy violations experienced by female social media users, understand the reasons behind these violations, the resulting effects, and examine preventive measures to protect privacy. The study sample was female users of social media, and its size reached 200individuals,The study results revealed that the most prevalent privacy violations encountered by female users included the use of obscene language, symbols, comments, or sexual jokes ,Sexual blackmail". Were among the most prominent reasons that made female users exposed to privacy violations " Sending pornographic videos and advertisement" "Joining more than one group on social media", "sharing feelings with others and their right of duty", and "feeling belonging to others".
(3CWQhMI (B((3eGLSJjQ(B)-(3LGeYI GdbGgQI, (B2024. s
(3HHdjhLQGajG(B: (3UaMGJ (B213-224.s
(3UOQ GjVG cbQU eOeLs
(3GdfU HGdYQHjI hGdedNU HGddZI GdEfLdjRjI hGdYQHjI(B.s
Keywords: (3hSGFd GdJhGUd GdELJeGYjs; (3GdNUhUjIs; (3Yde GLJeGY GdLQjeI s -- (3GfJgGc GdNUhUjIs -- (3GdNUhUjI GdeYdheGJjIs -- (3GdMjGI GdNGUIs -- (3hSGFd GdJhGUd GdGLJeGYis